Numerical investigation on cross-sectional temperature unbalance of bridge cables under fire heating - Li Zhang; Tong Guo; Yongsheng Song; Zekun Fan (Case Studies in Construction Materials)
This paper investigates the internal temperature variations of bridge cables under fire conditions. A finite element model of the cables was developed using ABAQUS, incorporating the effects of air between the steel wires. The model was validated through fire tests on two cable specifications (109 and 207). Two key indicators, the maximum temperature (Tmax) and the maximum temperature difference (TDmax), are critical for assessing the fire performance of bridge cables. Tmax represents the highest temperature the cable experiences during a fire, directly influencing the strength and load-bearing capacity of the cable material. Steel wires lose their strength at high temperatures, particularly as the temperature exceeds 550°C, which can lead to cable fracture or permanent deformation. In contrast, TDmax indicates the maximum temperature difference between individual steel wires within the cable during the fire. This temperature gradient can cause uneven expansion and result in cable failure. Using two key indicators, Tmax and TDmax, the effects of cable diameter, fire protection measures and their thicknesses, and heating curves on internal temperature variations across the cross-section of the bridge cables were analyzed. The study shows that for unprotected cables, as cable diameter increases, Tmax consistently appears at the outermost layer of the cable's steel wires, closely matching the highest ambient temperature. Additionally, TDmax increases nonlinearly with cable diameter. Adequate fire protection can significantly reduce both Tmax and TDmax. In unprotected cables, considerable temperature differences exist between the internal steel wires, whereas in protected cables, these differences are almost negligible. With sufficient fireproof material, TDmax can be reduced to below 300°C, and TDmax can be minimized to nearly 0°C. The model effectively predicts the internal temperature of cables under fire conditions, providing a basis for assessing fire-damaged cables and designing appropriate fire protection measures.